Synthesis, anti-fungal, anti-tumor and anti-inflammatory activities of some new 5-(N-substitutedarylidenehydrazono)-2-(4-chloroaryl) -3-oxo-1,2,4-thiadiazolidine - Manna P.; Narang K.K. (My University, 2025)
5-(N-Substitutedarylidenehydrazono)-2-(4-chloroaryl)-3-oxo-1,2,4- thiadiazolidines (IVa-e) have been synthesized by oxidative debenzylation and cyclization with bromine in chloroform from the corresponding 5-(4-chloroaryl)-1-(substitutedarylideneamino)-2-S-benzyliso-4-biurets (IIIa-e) or by the oxidation of corresponding 1-(substitutedarylideneamino)-5-(4-chloroaryl)-2,4-thiobiurets (Va-e), obtained from IIIa-e by reductive debenzylation with hydrogen sulphide in a mixture of pyridine and triethylamine. 2-S-Benzyliso-4-biurets (IIIa-e), in turn, were prepared by the condensation of 2-S-benzyliso-1-substitutedarylthiosemi-carbazone (IIa-e) with 4-chlorophenylisocyanate. Thiadiazolidines (IVa-e) have been characterized by their element analyses, IR, 1H-NMR and 13C-NMR. Anti-fungal screening of these compounds against ten fungi has been done by glass slides methods. The compound (1000 μg /ml) containing dichlorogroup IVe) showed maximum inhibitory effect (99.6 %) against Fusarium udum. The compound possessing dichloro group (IVe) have potent anti-inflammatory and anti-tumor properties as they down regulate NF-kB transcription factor.